Experimental Algorithms 9th International Symposium, SEA 2010, Ischia Island, Naples, Italy, May 20-22, 2010. Proceedings - Festa, Paola; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the 9th International Symposium on Experimental Algorithms, SEA 2010, held on Ischia Island, Naples, Italy, in May 2010. The 40 revised full papers presented together with two invited papers were carefully reviewed and selected from 73 submissions. The topics covered include algorithm engineering, algorithmic libraries, algorithmic mechanism design, analysis of algorithms, algorithms for memory hierarchies, approximation techniques, bioinformatics, branch and bound algorithms, combinatorial and irregular problems, combinatorial structures and graphs, communication networks, complex networks, computational geometry, computational learning theory, computational optimization, computer systems, cryptography and security, data streams, data structures, distributed and parallel algorithms, evaluation of algorithms for realistic environments, experimental techniques and statistics, graph drawing, heuristics for combinatorial optimization
Invited Papers -- Experimental Study of Resilient Algorithms and Data Structures -- Computational Challenges with Cliques, Quasi-cliques and Clique Partitions in Graphs -- Contributed Regular Papers -- Alternative Routes in Road Networks -- Fully Dynamic Speed-Up Techniques for Multi-criteria Shortest Path Searches in Time-Dependent Networks -- Space-Efficient SHARC-Routing -- A New Fully Dynamic Algorithm for Distributed Shortest Paths and Its Experimental Evaluation -- Contraction of Timetable Networks with Realistic Transfers -- Distributed Time-Dependent Contraction Hierarchies -- Practical Compressed Suffix Trees -- Maximum Cliques in Protein Structure Comparison -- Exact Bipartite Crossing Minimization under Tree Constraints -- Bit-Parallel Search Algorithms for Long Patterns -- Fast FPT Algorithms for Computing Rooted Agreement Forests: Theory and Experiments -- Experimental Evaluation of Approximation and Heuristic Algorithms for Sorting Railway Cars -- Time-Dependent Contraction Hierarchies and Approximation -- A New Combinational Logic Minimization Technique with Applications to Cryptology -- Randomized Rounding for Routing and Covering Problems: Experiments and Improvements -- The Time Dependent Traveling Salesman Problem: Polyhedra and Branch-Cut-and-Price Algorithm -- An Approximate ?-Constraint Method for the Multi-objective Undirected Capacitated Arc Routing Problem -- A Branch-and-Price Algorithm for Multi-mode Resource Leveling -- Experiments with a Generic Dantzig-Wolfe Decomposition for Integer Programs -- Using Bound Sets in Multiobjective Optimization: Application to the Biobjective Binary Knapsack Problem -- Improving Cutting Plane Generation with 0-1 Inequalities by Bi-criteria Separation -- New Lower Bounds for the Vehicle Routing Problem with Simultaneous Pickup and Delivery -- A Metaheuristic for a Two Echelon Location-Routing Problem -- New Fast Heuristics for the 2D Strip Packing Problem with Guillotine Constraint -- An Experimental Comparison of Different Heuristics for the Master Bay Plan Problem -- An Analysis of Heuristics for Vertex Colouring -- Automatic Tuning of GRASP with Path-Relinking Heuristics with a Biased Random-Key Genetic Algorithm -- Experiments with a Feasibility Pump Approach for Nonconvex MINLPs -- Paging Multiple Users in Cellular Network: Yellow Page and Conference Call Problems -- Realtime Classification for Encrypted Traffic -- Data Propagation with Guaranteed Delivery for Mobile Networks -- Data Structures Resilient to Memory Faults: An Experimental Study of Dictionaries -- Experiments on Union-Find Algorithms for the Disjoint-Set Data Structure -- Policy-Based Benchmarking of Weak Heaps and Their Relatives, -- Modularity-Driven Clustering of Dynamic Graphs -- Gateway Decompositions for Constrained Reachability Problems -- Robust and Efficient Delaunay Triangulations of Points on Or Close to a Sphere -- Fault Recovery in Wireless Networks: The Geometric Recolouring Approach -- Geometric Minimum Spanning Trees with GeoFilterKruskal -- Practical Nearest Neighbor Search in the Plane.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Storage and Retrieval; Database Management